U.S. agricultural policy: the 2002 Farm Bill and WTO DOHA Round proposal - Orden, David (International Food Policy Research Institute, 2003)
The 2002 U.S. farm bill has been widely criticized for increasing subsidies with detrimental effects on competing agricultural producers abroad and for undermining U.S. leadership in achieving liberalized world agricultural trade. This paper provides an assessment that shows the 2002 bill has effects that are nuanced in at least four respects. It raises expenditures compared to 1996 legislation, but not compared to actual 1998-2001 outlays. It maintains planting flexibility, but extends support to new crops and undermines some of the decoupling of subsidy payments from production and market prices that had occurred. It violates the spirit of U.S. trade liberalization rhetoric, but probably not the letter of U.S. WTO commitments. And it continues the policies of wealthy countries that collectively distort agricultural production and world prices, but only marginally worsen the net effects of these policies.